Base excision repair - Moldave, Kivie, 1923-; Mitra, Sankar (Progress in nucleic acid research and molecular biology ;, 2001)
This volume of Progress in Nucleic Acid Research and Molecular Biology represents research discussed during the DNA Base Excision Repair Workshop. This compilation of articles focuses on several recent observations highlighting the complexity of the base excision repair (BER) process in DNA repair. Focusing on the various facets of BER research, this book is a timely and highly beneficial reference for investigators in the DNA repair field. It will also aid scientists not directly involved in repair studies to obtain a comprehensive understanding of the current state of knowledge in the field. Progress in Nucleic Acid Research and Molecular Biology provides a forum for discussion of new discoveries, approaches, and ideas in molecular biology. It contains contributions from leaders in their fields and abundant references. Key Features *Provides a forum for discussion of new discoveries, approaches and ideas in molecular biology. * Presents contributions from top researchers * Includes abundant references.